The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1442-200x.2004.01880.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal enterotoxin‐specific IgE antibodies in atopic dermatitis

Abstract: Atopic dermatitis patients who exhibit high positive rates of SEA/SEB-specific IgE antibodies were found to be school children, severe cases, cases with high serum concentrations of total IgE, cases with exacerbation in summer, and cases with dogs and/or cats as pets. The measurement of serum concentrations of specific IgE antibodies to SEA and SEB, thus has some value for evaluating AD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 18 publications
1
31
0
1
Order By: Relevance
“…More recently, other investigators found that in 140 pediatric patients with AD, 47 patients (33.6%) had IgE specific for either SEA or SEB. The patients with more severe AD had higher positive rates than those with milder disease [25].…”
Section: Ige Antibodies To Microorganismsmentioning
confidence: 99%
“…More recently, other investigators found that in 140 pediatric patients with AD, 47 patients (33.6%) had IgE specific for either SEA or SEB. The patients with more severe AD had higher positive rates than those with milder disease [25].…”
Section: Ige Antibodies To Microorganismsmentioning
confidence: 99%
“…3). The same exotoxins with superantigenic properties may also be a target for IgE responses in AD patients [60]. The levels of HBD-2 and the cathelicidin LL-37-as well as IL-8 and inducible NO synthetase (iNOS)-were found to be reduced in AD compared to psoriasis patients [47,61].…”
Section: Staphylococcus Aureus and Atopic Dermatitismentioning
confidence: 98%
“…Antigen-specific immune response to aero-and food allergens involving IgE-mediated, facilitated antigen presentation colocalize with polyclonal activation of T cells driven by superantigenic properties of staphylococcal exotoxins [3], which may also be a target for IgE responses in AD patients [81].…”
Section: Innate Immunity and Staphylococcus Aureus Colonizationmentioning
confidence: 99%